A cross-cultural and linguistic perspective on Uzbek and English proverbs. (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article explores the cultural and linguistic significance of proverbs in shaping and reflecting national identity, focusing on a comparative analysis of Uzbek and English proverbs. It highlights how proverbs encapsulate cultural values such as hospitality, resilience, justice, unity, and hard work in Uzbek society, acting as a vessel for transmitting collective wisdom and identity. Through a cross-cultural lens, the paper also identifies common thematic elements in both English and Uzbek proverbs, illustrating shared human experiences despite linguistic and historical differences. The study emphasizes the role of proverbs as a bridge between cultures, offering valuable insights into societal values and ethical principles across linguistic boundaries.